Developing sustainable internal communications systems in the entrepreneurial environment: Empirical and statistical analysis - Sančanin Branislav; Penjišević Aleksandra (Trendovi u Poslovanju)
In establishing a new organizational system and methods of work, it is necessary to inform employees about all issues important for its functioning. If that kind of approach is absent, it can easily happen that employees from the start react with resistance and mistrust due to misinformation regarding the goals, both organizational, and individual. Such a lack of honest and open communication within the organization made the flow of information difficult or nonexistent. In order to build a sustainable internal communication system and thus restore employees' confidence in the future, it is essential that any initiative of this kind starts from the leadership. Towards the solution to the problem of internal communication two potential models can be applied: a) the transparency of information, or b) two-way communication. Information transparency refers to the organizations where employees already have a high level of confidence in the leadership and its decisions, so that the information they receive is considered as relevant and true. On the other hand, the process of two-way communication should be applied to build or re-build trust and connect employees to the organization and leadership. In this research, the sample was purposive for employees in small and mediumsized enterprises on the territory of the Republic of Serbia (n=152). It was established that employees evaluate the relationship with the direct manager better than the understanding of their own problems by the direct manager. Older respondents have a better relationship with their direct managers. Respondents who have a total working experience of 21-30 years rate the communication with their direct manager somewhat worse.